Improving the reliability of the energy system Uzbekistan under the conditions of “green” transition - Shuxrat V. Xamidov; Iskander M. Buranov; Bahrom R. Normuratov (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: Considering the large-scale integration plans for renewable energy sources (RES) into the Unified Power System (UPS) of Central Asia, it is essential to address the issue of maintaining the balance between electricity generation and consumption. The intermittent nature of RES-based electricity generation can significantly affect the operational stability of the power interconnection. This study examines modern energy storage systems aimed at reducing the likelihood of uncompensated power imbalances and enhancing the reliability of power supply to consumers. The analysis identifies the types of energy storage systems most suitable for implementation in Uzbekistan and evaluates the potential for covering energy deficits through RES integration. Aim: study of the possibilities for enhancing the flexibility and reliability of Uzbekistan's power system during the transition to green energy, identification of potential imbalance and stability issues in the system amid large-scale integration of renewable energy sources, as well as evaluation of the effectiveness of modern technological solutions to address them, including energy storage systems and other supporting tools. Methods: the implementation of advanced control systems such as SCADA/EMS, Smart Grid, and Virtual Power Plants (VPPs) was assessed, along with their real-time impact on the power system. These technologies were used to study the adaptive management of renewable energy sources within the system. Results: the rapid and large-scale integration of renewable energy sources (RES) is creating new challenges for Uzbekistan's power system. In particular, imbalances between generation and consumption, frequency fluctuations, and voltage instability reduce the system's overall stability.